Modification of soil modeling and using it in the fish-bone model - A. H. Jafarieh; H. Khosravi; T. Fazelifar (مهندسی عمران شریف)
The basic design of any structure requires sufficient and detailed modeling of each structural element. It must be taken into consideration that the modeling of each member of the structure and performing nonlinear dynamic analysis due to the presence of multiple degrees of freedom, is time-consuming. Therefore, a wide range of structures cannot be investigated. To resolve this issue, researchers have recommended using simplified equivalent models to study a wide range of structures, provided that the equivalent ones significantly reflect the behavior of the original structure. One of these models is the fishbone model, which is used for modeling moment-resisting steel structures and it also has a suitable accuracy. Additionally, the presence of soil can significantly change the response of the structure. This is despite the fact that accurate modeling of the soil will lead to an increase in degrees of freedom. In this study, the aim is to examine the seismic performance of soil-structure systems to evaluate the accuracy of the models presented in seismic codes, and after modification, provide a simplified model for placement under the fishbone frame. In this regard, first by modeling a number of foundations on distributed Winkler springs considering nonlinear behavior for the soil, the moment-rotation capacity curve of the foundations was drawn, and then the aforementioned graphs were simplified into bilinear curves through an algorithm. The bilinear models that are presented, have greater stiffness and strength compared to the model presented by the seismic code. Two equations were suggested for determining the coefficients of the bilinear model by regression. In the next step, instead of modeling vertical distributed springs beneath the foundation, a rotational spring with modified bilinear behavior was placed under the fishbone model. The analysis of the seismic response of soil-structure systems under earthquake records shows that using the modified model instead of the model presented in the seismic code leads to responses with appropriate accuracy. In addition, by using the modified model, the time required for the time history analysis is noticeably reduced, which is important in research studies.